PERANCANGAN DAN PEMBUATAN ALAT UKUR UNTUK PEMETAAN KONTUR POKET DALAM DENGAN MENGGUNAKAN SENSOR ULTRASONIK - Nugroho, Oktavianus Ardhian; Aditya, Evan (BAROMETER, 2023)
In this's era, the measuring instruments used in the machining process still use a lot of mechanical principles and there are only a few that are combined with electrical components. Most of the measuring instruments that exist now are only linear and there are still few that can measure the shape of the contour. One of the tools that can be used to measure contours is CMM, but the price of this tool is very expensive. The need for tools for this contour measurement process is very much needed in the industrial world because some parts of the industry have various contour shapes and are difficult if measured without using a CMM machine. Therefore, the purpose of this study is to make a measuring instrument for contour mapping using electronic sensors. The manufacture and design of measuring instruments start with designing electricity and hardware, then continues with microcontroller programming and Matlab. This measuring instrument is then tested for linear distance measurement accuracy, accuracy per angle, and accuracy of contour shapes. The results showed that the size results had a maximum deviation of 10 millimeters with a maximum distance of 500 millimeters. The 0° angle is the worst reading angle with a deviation of 8.67 millimeters, while the 90° and 180° angles are the best reading angles with a deviation of 1 millimeter. Square and rectangular shapes can be represented quite well, while triangular shapes are less well represented due to their angles being far from perpendicular to the sensor.